MONITORING KINEJA DOSEN :Manfaat Dan Dampaknya Terhadap Perguruan Tinggi - Endang Sugiarti; Mukrodi Mukrodi; Syamsi Mawardi (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Monitoring Lecturer Performance: Benefits and Impact on Higher Education, this study aims to analyze Unpam Lecturer Performance Monitoring Based on the Tri Dharma of Higher Education, to find out how the impact of Unpam Lecturer Performance Monitoring, to find out how the impact of Unpam Lecturer Performance Monitoring. This type of research is an evaluative research using qualitative methods. The informants used in the research are informants who have been determined by the researchers, namely people who are authorized to convey the information. Data were collected by means of in-depth interviews, direct observation and document review. The research instruments used were interview guides, observation sheets, and documentation sheets. The results show that the performance of Pamulang University lecturers is quite good, there are only a few findings that must be improved, such as in terms of functional positions that need to be improved, lecturer certification needs to be achieved and research on grants for higher education needs to be maximized.